INDIVIDUAL FACTORS THAT INFLUENCE THE ETHICAL BEHAVIOR OF ACCOUNTING STUDENT - Kusvanti, HeniIkke; Suhendro, Suhendro; Dewi, Riana R (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2019)
This research aims to find out how the influence of gender, ethical sensitivity, locus of control, and the understanding of the code of ethics the ethical behaviour against the accountant accounting students at universities in Surakarta. The population in this research are undergraduate students program of study had been completed accounting auditing courses at the Islamic University of Surakarta Batik, Slamet Riyadi, University and high school Economics. Sampling technique used was simple random sampling technique. Methods of analysis used was multiple linear regression analysis. The results of this research show that gender, ethical sensitivity and locus of control have no effect against the ethical behavior of college students in Surakarta. While the understanding of the code of ethics to ethical behavior of college students in Surakarta. The value of the coefficient of determination (R2) of 0.102. This indicates that the variansi variable on the practice of ethical behavior of college students in higher education in Surakarta amounted to 10.2% can be explained by the variable gender, ethical sensitivity, locus of control and understanding of the code of ethics of accountants, while the rest 89.8% is explained by factors – factors other than that examinedThis research aims to find out how the influence of gender, ethical sensitivity, locus of control, and the understanding of the code of ethics the ethical behaviour against the accountant accounting students at universities in Surakarta. The population in this research are undergraduate students program of study had been completed accounting auditing courses at the Islamic University of Surakarta Batik, Slamet Riyadi, University and high school Economics. Sampling technique used was simple random sampling technique. Methods of analysis used was multiple linear regression analysis. The results of this research show that gender, ethical sensitivity and locus of control have no effect against the ethical behavior of college students in Surakarta. While the understanding of the code of ethics to ethical behavior of college students in Surakarta. The value of the coefficient of determination (R2) of 0.102. This indicates that the variansi variable on the practice of ethical behavior of college students in higher education in Surakarta amounted to 10.2% can be explained by the variable gender, ethical sensitivity, locus of control and understanding of the code of ethics of accountants, while the rest 89.8% is explained by factors – factors other than that examined